(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The competitiveness of each product mostly depends on its price, which includes transport costs from the place of its production to the place of its consumption. Sometimes these costs can be comparable the cost of production. Due to the high transport costs, the competitiveness of the manufactured products decreases, not only on the domestic but also on the foreign market. Substantial part of the freight transport nationwide is carried out by trucks owned by the manufacturing companies. They transport goods needed for their production needs with their own transport and at their own expense. At the same time, the operational planning of such shipments has been insufficiently studied, in which a large number of factors of technological and organizational nature must be taken into account. Operational planning has a significant potential for reducing transportation costs. The article considers the possibility to increase the efficiency of own-account transport at the stage of operational planning.